Advances in Front-end Enabling Technologies for Thermal Infrared ‘THz Torch’ Wireless Communications - Hu,F; Lucyszyn,S (Journal of Infrared, Millimeter, and Terahertz Waves, 2016)
The thermal (emitted) infrared frequency bands (typically 20-40 THz and 60-100 THz)are best known for remote sensing applications that include temperature measurement (e.g., noncontactingthermometers and thermography), night vision and surveillance (e.g., ubiquitous motionsensing and target acquisition). This unregulated part of the electromagnetic spectrum also offerscommercial opportunities for the development of short-range secure communications. The ‘THzTorch’ concept, which fundamentally exploits engineered blackbody radiation by partitioningthermally-generated spectral radiance into pre-defined frequency channels, was recentlydemonstrated by the authors. The thermal radiation within each channel can be independently pulsemodulated,transmitted and detected, to create a robust form of short-range secure communicationswithin the thermal infrared. In this paper, recent progress in the front-end enabling technologiesassociated with the ‘THz Torch’ concept is reported. Fundamental limitations of this technology arediscussed; possible engineering solutions for further improving the performance of such thermalbasedwireless links are proposed and verified either experimentally or through numericalsimulations. By exploring a raft of enabling technologies, significant enhancements to both data rateand transmission range can be expected. With good engineering solutions, the ‘THz Torch’ conceptcan exploit 19th century physics with 20th century multiplexing schemes for low-cost 21st centuryubiquitous applications in security and defence.